PCR for diagnosis and assessment of cure in kala-azar patients in Bangladesh - Salam, Md. Abdus; Mondal, Dinesh; Kabir, M.; Ekram, A.R.M.S.; Haque, Rashidul (2010)
The study evaluated the usefulness of Leishmania-nested polymerase chain reaction (Ln-PCR) for diagnosis of kala-azar and assessed its role as a test of cure among kala-azar patients in Bangladesh. Peripheral blood buffy coat Ln-PCR was done in ninety-seven (97) clinically suspected patients of kala-azar, in forty (40) healthy controls from both endemic and non-endemic areas, and in forty-six (46) patients after completion of treatment with sodium stibogluconate (SSG). The Ln-PCR results were compared with Leishmania donovani parasite load graded by 1+ to 6+ in all smear-positive L. donovani cases. Out of 97 clinically suspected kala-azar patients, 94 were parasitologically confirmed. Ln-PCR was found positive in 91 of 94 parasitologically positive patients of kala-azar at diagnosis, indicating its diagnostic sensitivity as 97%. None of the controls was found positive for Ln-PCR, indicating its diagnostic specificity to be 100%. About 9% of kala-azar patients having been graded 1+ parasitic load had negative Ln-PCR results. After completion of treatment, Ln-PCR was positive in 4 patients (8.4%) out of 46 cases, indicating its role in demonstrating the absence of parasites 30 days after completion of treatment in 91.6% of the treated patients. This limited study suggests that Ln-PCR is a highly sensitive and specific test for the diagnosis of visceral leishmaniasis and can be used as a test of cure. Thus, efforts should be made to establish this useful method at least in the tertiary care hospitals and, if possible, at the district-level hospitals, especially in the endemic areas of Bangladesh.